2017
DOI: 10.4038/cjs.v46i3.7439
|View full text |Cite
|
Sign up to set email alerts
|

Conservational significance of Dunumadalawa Forest Reserve in Central Sri Lanka based on the endemism of its avifauna

Abstract: Abstract:The concept of endemism is useful in evaluating the biological significance and uniqueness of an area. It is a meaningful alternative to simple species richness and can be used as a relevant measure in assessing conservational significance. Dunumadalawa (7 o 17'00"N; 80 o 38'49"E; 548-972 m above sea level) is a semi-isolated, hill country wetzone forest reserve located in Kandy District, Sri Lanka. It is approximately 480 ha in extent, and comprises mainly of secondary growth forest. The objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…The 74 species of birds recorded from the EPA represents about 16% of the island's total bird species. This indicate that the species richness in this EPA is higher than those reported in many other areas around Kandy city limits (Karunaratna 1986;Wijesundara & Santiapillai 2001;Ellepola 2014;Weerakoon 2015;Hettiarachchi & Wijesundara 2017). However, the bird species richness in Warathenna-Hakkinda EPA is lower than what is recorded in the Gannoruwa Forest Reserve (84 species) which is located adjacent to the EPA with an extent of 2.1 km 2 (Rathnayake et al 2016).…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The 74 species of birds recorded from the EPA represents about 16% of the island's total bird species. This indicate that the species richness in this EPA is higher than those reported in many other areas around Kandy city limits (Karunaratna 1986;Wijesundara & Santiapillai 2001;Ellepola 2014;Weerakoon 2015;Hettiarachchi & Wijesundara 2017). However, the bird species richness in Warathenna-Hakkinda EPA is lower than what is recorded in the Gannoruwa Forest Reserve (84 species) which is located adjacent to the EPA with an extent of 2.1 km 2 (Rathnayake et al 2016).…”
Section: Discussioncontrasting
confidence: 54%
“…In addition, it represents 26% of endemic bird species of the island (MOE 2012;Gabadage et al 2015), while only 11 endemic species have been recorded from the Gannoruwa forest (Rathnayake et al 2016). The number of endemic species is a measure that can predict the amount of human influence (Linder 1995;BirdLife International 2008;Hettiarachchi & Wijesundara 2017). Typically, undisturbed natural forests in the wet zone harbor many endemic species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The habitat heterogeneity hypothesis suggests that a landscape's species diversity increases with the number of habitats because of an expansion in the number of partitionable niche dimensions (Cramer & Willing 2005;Chakdar et al 2016). Numerous studies have revealed that the distribution and diversities of bird species were highly dependent on habitat heterogeneity (Hettiarachchi & Wijesundara 2017;Chandrasiri et al 2018;Panda et al 2021;Thilakarathne et al 2021).…”
Section: Discussionmentioning
confidence: 99%